White noise’s effect on premature infants’ physiological parameters during peripheral intravenous catheter insertion - Omolbani Rahimi; FatemehSadat SeyedNematollah Roshan; Leila Nikrouz (BMC Pediatrics)
Abstract Background Early and continuous exposure to painful stimuli in premature infants leads to short-and long-term complications. Listening to white noise is an accessible and inexpensive non-invasive method that can be used as a safe nursing intervention in hospitals. This study aimed to assess white noise’s effect on premature Infants’ physiological parameters during peripheral intravenous catheter insertion. Methods The present experimental study was conducted on 40 premature Infants. From 5 min before Indwelling catheters to 10 min after, white noise was played through headphones to infants at a controlled volume in the test group. Using a monitor, physiological parameters were recorded from 10 min before to 30 min after the Indwelling catheter. Statistical analysis was done through the SPSS version 27 software program. Results Regarding respiratory rate, there was no statistically significant difference between the two groups in the first, second, and sixth stages (p < 0.05). However, in the third, fourth, and fifth stages, RR in the control group was significantly higher than the test group (p ≤ 0.05). In terms of mean arterial blood pressure, there was no statistically significant difference between the two groups in any of the stages (p < 0.05). In terms of heart rate, there was no statistically significant difference between the two groups in the first, second, and sixth stages (p < 0.05). However, in the third, fourth, and fifth stages, HR in the control group was significantly higher than the test group (p ≤ 0.05). Regarding oxygen saturation percentage, there was no statistically significant difference between the two groups in the first, second, third, and sixth stages (p < 0.05). In contrast, in the fourth and fifth stages, the oxygen saturation percentage in the test group was significantly higher than in the control group (p < 0.05). Conclusions Although in both groups the painful procedure led to an increase in physiological variables (respiratory rate, heart rate, mean arterial blood pressure) and a decrease in blood oxygen saturation, in the test group these variables approached their initial state more quickly within half an hour after exposure to white noise. This confirms that the effect of white noise on the improvement of physiological variables is gradual. Clinical trial number Not applicable.